Суть суспільно небезпечного посягання в контексті підстави необхідної оборони - Андрусяк, Ганна Миколаївна (Волин. нац. ун-т. ім. Лесі Українки, 2020)
У статті обгрунтована правильність визначення підстави необхідної оборони як суспільно небезпечного посягання. Визначено семантику поняття «підстава», адже цей термін є багатозначним. Проаналізована наукова дискусія щодо можливості необхідної оборони проти посягання, шо є бездіяльністю. У статті обгрунтована правильність визначення підстави необхідної оборони як суспільно небезпечного посягання. Визначено семантику поняття «підстава», адже цей термін є багатозначним. Проаналізована наукова дискусія щодо можливості необхідної оборони проти посягання, шо є бездіяльністю. The article substantiates the correctness of determining the basis of necessary defense as a socially dangerous encroachment. In focus is the semantics of the concept of necessity, because the term is rather ambiguous. The author highlights the scientific discussion on the admissibility of necessity defense against encroachment, which is not in action. According to the author, in case of the necessary defense, the encroachment should threaten the state or public interests, political, labor, and property rights of citizens or individuals, their honor and dignity. Only in these contexts, it can be classified as socially dangerous. Other forms of encroachment, not only an attack, can be interpreted as socially dangerous and a reason for the necessary defense. Since the law involves the prevention or cessation of a person's attempt to commit an act that presents a public danger, it obviously implies a certain activity of the person. The law does not read that encroachment is always combined with violence – it must be just socially dangerous. Among all the circumstances that exclude the criminality of the act, only the necessity defense is a reaction to a socially dangerous encroachment, which is possible both in an active form and in a passive one
The Essence of Socially Dangerous Encroachment in the Context of the Necessity Defense
Keywords: необхідна оборона; напад; підстава необхідної оборони; суспільно небезпечне посягання; бездіяльність; necessary defense; attack; reason for necessity defense; socially dangerous encroachment; inaction